Long-term decline of the mid-infrared emission of normal galaxies: dust echo of tidal disruption flare?. Issue 3 (4th May 2018) - Wang, Tinggui; Yan, Lin; Dou, Liming; Jiang, Ning; Sheng, Zhenfeng; Yang, Chenwei
Abstract: We report the discovery of a sample of 19 low-redshift ( z < 0.22) spectroscopically non-Seyfert galaxies that show slow declining mid-infrared (MIR) light curves (LCs), similar to those of tidal disruption event (TDE) candidates with extreme coronal lines. Two sources also showed relatively fast-rising MIR LCs. They consist of a 61 per cent sample of Wide-field Infrared Survey Explorer ( WISE ) MIR variable non-Seyfert galaxies with Sloan Digital Sky Survey (SDSS) spectra. In a comparison sample of optically selected Seyfert galaxies, the fraction of sources with such a LC is only 15 per cent. After rejecting five plausible obscured Seyfert galaxies with red MIR colours, the remaining 14 objects are studied in detail in this article. We fit the declining part of the LC with an exponential law and the decay time is typically one year. The observed peak MIR luminosities (ν L ν ) after subtracting host galaxies are in the range of a few 10 42 –10 44 erg s −1, with a median of 5 × 10 43 erg s −1 in the W 2 band. The black hole masses are distributed over a wide range, with more than half between 10 7 and 10 8 M⊙, but are significantly different from those of optical/UV selected TDEs. Furthermore, MIR luminosities are correlated with the black hole mass, stellar mass or luminosity of their host bulges. Most galaxies in the sample are red and luminous, with an absolute r magnitude between −20 and −23. We estimate the rate of event as about 10 −4 galaxy −1 yr −1 among luminous red galaxies. We discuss several possibilities for variable infrared sources and conclude that most likely they are caused by short sporadic fuelling of supermassive black holes via either the instability of accretion flows or tidal disruption of stars.